Cu supraparticles with enhanced mass transfer and abundant C-C coupling sites achieving ampere-level CO2-to-C2+ electrosynthesis - Lushan Ma; Hong Liu; Bingbao Mei; Jing Chen; Qingqing Cheng; Jingyuan Ma; Bo Yang; Qiang Li; Hui Yang (Nature Communications)
Abstract The efficient electrochemical CO2 reduction to C2+ products at high current densities remains a significant challenge. Here we show inherently hydrophobic and hierarchically porous Cu supraparticles comprising sub-10 nm Cu constituent particles for ampere-level CO2-to-C2+ electrosynthesis. These supraparticles feature abundant grain boundaries for high C2+ selectivity, coupled with interconnected mesopores and interparticle macropore cavities to enhance the accessibility of the active sites and mass transfer, breaking the trade-off between activity and mass transfer in Cu-based catalysts. Moreover, the intrinsic hydrophobicity of the supraparticles mitigates the water-flooding issue of catalytic layer in flow cells, improving the stability at high current densities. Consequently, the Cu supraparticles achieve ampere-level CO2 electrolysis up to 3.2 A cm-2 with a C2+ Faradaic efficiency of 74.9% (compared to 1.21 A cm-2 and 55.4% for Cu nanoparticles) and maintain stability at 1 A cm-2 for over 100 h. This work provides profound insights into the effect of the coupling of mass transfer and catalytic reaction under a high current and presents a corresponding solution by superstructure design.